FACTORS DETERMINING THE CHOICE OF UNIVERSITY BY CANDIDATES - Szeląg-Sikora, Anna; Oleksy-Gębczyk, Aneta; Kowalska-Jarnot, Katarzyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The presence of non-public schools on the polish higher education market has led to increased competition and constituted a fundamental incentive to introduce marketing management in universities, both public and private. The educational services market is dominated by price competition, supported by promotional activities. Image and price are the two most important reasons for taking up studies at a given university, and the image is a particularly important source of building a university's competitive advantage. However, between public and private universities in Poland, there are significant differences in terms of image structure. The aim of this article is to examine what identity factors are decisive for candidates, what sources of information about the university were most important for candidates.